Nanostructure changes in diesel soot during NO2–O2 oxidation under diesel particulate filter-like conditions toward filter regeneration. (October 2019) - Singh, Madhu; Srilomsak, Mek; Wang, Yujun; Hanamura, Katsunori; Vander Wal, Randy
Development of the regeneration process on diesel particulate filters requires a better understanding of soot oxidation phenomena, especially its relation to soot nanostructure. Nitrogen dioxide (NO2 ) is known to play an essential role in passive regeneration by oxidizing soot at low temperatures, especially in the presence of oxygen (O2 ) in the exhaust. However, change in soot nanostructure due to oxidation by NO2 –O2 mixtures has not received much attention. This work focuses on nanostructure evolution during passive regeneration of the diesel particulate filter by oxidation of soot at normal exhaust gas temperatures (300°C–400°C). High-resolution transmission electron microscopy of partially oxidized model carbons (R250, M1300, arc-generated soot) and diesel soot under NO2 –O2 mixtures is used to investigate physical changes in nanostructure correlating with the material's behavior during oxidation. Microscopy reveals the changing nanostructure of model carbons during oxidation while fringe analysis of the images points to the differences in the structural metrics of fringe length and tortuosity of the resultant structures. The variation in oxidation rates highlights the inter-dependence of the material's reactivity with its structure. NO2 preferentially oxidizes edge-site carbon, promotes surface oxidation by altering the particle's burning mode with increased overall reactivity of NO2 +O2 resulting in inhibition of internal burning, typically observed by O2 at exhaust gas temperatures.